(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study determined the influence of play-based strategies on the social and cognitive growth of preschool children in public early childhood schools in Danao City during the school year 2024–2025. With a descriptive-correlational research design, the study utilized 40 preschool teachers utilizing purposive sampling. Data were gathered utilizing a validated observation-based measure of instructional practices and child development indicators. Findings indicated that the teachers applied play-based strategies with high frequency, most significantly those that supported creativity, social interaction, and expressive communication. Such instructional practices were associated with measurable gains in children’s reasoning power, language usage, emotional intelligence, and cooperative behavior. Statistical analysis indicated a statistically significant positive relationship between implementation level of guided play and cognitive-social developmental outcomes, upholding Vygotsky’s Sociocultural Theory. Although the positive results are comforting, however, the study found the following challenges: generational differences between teachers and absence of parental involvement, which hindered optimal maximization of the advantage of play-based learning. In response, the study suggested a Preschool Success Nurturing Connections Initiative to foster teacher competence, enhance home-school partnership, encourage open communication, and utilize structured progress monitoring. In summary, the findings reaffirm the central role of purposeful, developmentally responsive play in cultivating integral early childhood development and necessitate policy and practice frameworks that enshrine meaningful play as the cornerstone of preschool education.